Notes from Bruce Ehresman, 22 July - Ehresman, Bruceet al (1998)
An annotated list of birds sighted by Bruce Ehresman dated July 22, 1998. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1998.